A three-dimensional plasmonic spacer enables highly efficient solar-enhanced membrane distillation of seawater. Issue 17 (9th April 2019) - Ang, Edison Huixiang; Tan, Yong Zen; Chew, Jia Wei
Abstract : A 3D plasmonic spacer for membrane distillation: rational-design of a 3D spacer with nano-gaps in plasmonic hybrids for localized heating could enhance the distillate flux and reduce energy consumption of membrane distillation. Abstract : Herein, we demonstrate an energy-efficient means for water desalination using a three-dimensional (3D) porous spacer for plasmon-enhanced solar membrane distillation (MD). This unique spacer rationally designed from noble metals, which generates 60 l m −2 of fresh water per day, had a photothermal efficiency of 98% (under 0.8 sun).